Training support scheme on organic rice production in Lao PDR - Choulatida, Phetsoulaphonh N. (USM R & D Journal, 2011)
The study examined the activities of 152 certified organic rice farmers in 10 villages in Sangthong district, Lao PDR using structured interviews in 2009. Three training providers namely: ORFC, government agencies, and ProRice participated in focused-group discussion. Results showed that the trainings that government agencies provided were highly appreciated at 68.3%, compared to the training provided by ProRice (58.6%) and ORFC (50.3%). Relevance of content and coherence of topics on farm operation were significant determinants of farmer's satisfaction. A considerable segment of the respondents (47.27%) expressed disappointment on topics which were part of the original training topics but were not actually discussed or provided. On the other hand, 56.86% of respondents claimed that some training included topics which were not presented in the original plan but results of these kinds of training were fairly successful. Another 54.51% claimed that the trainings failed because there was no opportunity for hands-on training of the knowledge skills that the farmers had obtained. In terms learning levels, the average knowledge development of respondents were quite high particularly on topics on compounding of rice growing, farm record keeping, organic standard operating, etc. Still, farmers expressed felt training needs in the listed training topics. Results show that organic agricultural development and farmer empowerment in Sangthong district may be achieved through adequate training in the identified areas.